Two new species of Bonamia (Convolvulaceae) endemic to the Brazilian Cerrado - Moreira, André Luiz Da Costa; Simão-Bianchini, Rosangela; Cavalcanti, Taciana Barbosa (Phytotaxa, 2018)
Two new endemic species of Bonamia Thours (Convolvulaceae) are described from the Brazilian Cerrado: Bonamia austinii A.Moreira & Sim.-Bianch., and Bonamia krapovickasii A.Moreira & Sim.-Bianch. Both species grow in Campo Limpo (savanna grassland with few scattered trees) and have small tomentose leaves and white flowers. They are easily distinguished from each other and from other species of the genus by their habit and inflorescence. The new taxa are illustrated and their characteristics are compared with morphologically similar species.